Pengaruh Kenaikan Tarif Pajak Pertambahan Nilai (PPN) Terhadap Perilaku Konsumen Dan Minat Beli Konsumen di Top Mode Makassar - Jumra Jumra; Rifqi Nur Wahyudi (Journal Axegnal: Tax And Economic Insights Journal, 2026)
This study aims to analyze the effect of an increase in Value Added Tax (VAT) rates on consumer behavior and consumer purchasing interest at the Top Mode retail store Makassar. The main problem studied is how the  VAT rates affects consumer behavior and purchasing decisions at the store. The study uses a quantitative approach with primary data obtained through questionnaires and secondary data from related documents. The analysis technique used is simple linear regression to measure the relationship between the increase in VAT 1rates and consumer behavior and purchasing interest. The results of the study indicate that the 11% increase in VAT rates has a positive and significant effect on consumer behavior and purchasing interest. Even though the price of goods has increased, consumers at Top Mode still make purchases by adjusting their behavior, such as being more selective and taking advantage of promotions. This finding confirms that an increase in VAT rates does not always reduce purchasing interest, but rather triggers consumer adaptation in making purchasing decisions. Therefore, stores need to optimize their marketing strategies to maintain and increase purchasing interest amidst changes in tax rates.